Magnetic Behavior of Single La0.67Ca0.33MnO3 Nanotubes: Surface and Shape Effects - Dolz, M.I.; Bast, W.; Antonio, D.; Pastoriza, H.; Curiale, J. Sánchez, R. D.; Leyva, A. G. (AIP Publishing, 2008)
Fil: Dolz, M.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Universidad Nacional de San Luis. Departamento de Física; Argentina